Neuroprotective effects of baicalin and baicalein on the central nervous system and the underlying mechanisms - Lujia Si; Yupu An; Jiahang Zhou; Yu Lai (Heliyon)
Baicalin and baicalein are the primary flavonoids derived from the desiccated root of Scutellaria baicalensis, which is a member of the Lamiaceae family; these flavonoids have diverse pharmacological properties and show significant potential for the management of central nervous system disorders. Multiple studies have indicated that these substances effectively reduce the severity of illnesses such as depression, stroke, and degenerative disorders of the central nervous system by exerting antioxidant and anti-inflammatory effects, regulating programmed cell death, and reducing mitochondrial malfunction. Recent studies have highlighted the connection between the accumulation of iron and the ability of baicalein to protect the nervous system. Given the diverse therapeutic effects of baicalein, this review aims to thoroughly investigate the regulatory pharmacological mechanisms through which baicalein influences the development of central nervous system disorders. By elucidating these mechanisms, this review contributes to the development of therapeutic approaches that target disorders of the central nervous system.